FUTURE WATER MANAGEMENT PROBLEMS IN ASIAN MEGACITIES - Prinz, Dieter; Juliani, Any; Brontowiyono, Widodo (Jurnal Sains Dan Teknologi Lingkungan, 2009)
Today, about half of the world population lives in urban areas and in the coming 20 years, urbanization isexpected to increase steadily, especially in the Developing World. Based on UN data and projections, about4 out of the 5 billion world urban population will live in developing countries by 2030. Large cities in theDeveloping World face the problem of unplanned growth, coupled with the financial and operationalinability to offer the public services needed to sustain a decent life in urban environments. Water is one ofthose essential commodities which is often short in supply and/or of low quality. Additionally, flood poses athreat to urban dwellers during rainy season. The water management challenges in tropical urban areastoday and in the decades to come can be characterized by (1) fighting physical shortcomings in waterresources, (2) coping with contamination of groundwater, rivers, lakes, and reservoirs by domestic,agricultural or industrial waste and waste water, (3) mitigating environmental impacts of water extraction(such as loss of wetlands, subsidence and seawater intrusion) , (4) preventing / mastering flood situationsand (5) overcoming administrative and financial strains and operational incapacities. Solutions to theproblems of urban water in 20 years time are to be found in supply side and demand side measures. The firstgroup includes (1) optimal use of surface water and groundwater resources, (2) pollution protection, (3)watershed management and (4) more water storage. The second group includes (1) educational training, (2)technological innovation, (3) water conservation and (4) water pricing.